2015
DOI: 10.1007/s11060-015-1737-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of anaplastic transformation in low-grade oligodendrogliomas based on magnetic resonance spectroscopy and 1p/19q codeletion status

Abstract: The aim of this study was to assess whether combining multimodal magnetic resonance imaging (MRI) with the determination of the 1p/19q codeletion status could improve the ability to predict anaplastic transformation in low-grade oligodendrogliomas. Twenty patients with grade II oligodendrogliomas were followed-up using multimodal MR [proton MR spectroscopy (MRS), perfusion, and conventional MR imaging]. All patients diagnoses were histologically proven, and 1p/19q codeletion status was analyzed for all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In agreement with this finding, early patterns of high-grade glioma infiltration using DWI and DTI were reported [ 21 , 35 , 36 ], however, in these studies the scalar indices were not visualized. Our findings are further substantiated by the fact that both MR-spectroscopy [ 23 , 25 ] and perfusion MRI [ 24 , 37 ] may detect abnormalities before CE appears. In conclusion, AD may depict the correlate for these early metabolic and micro-vascular changes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In agreement with this finding, early patterns of high-grade glioma infiltration using DWI and DTI were reported [ 21 , 35 , 36 ], however, in these studies the scalar indices were not visualized. Our findings are further substantiated by the fact that both MR-spectroscopy [ 23 , 25 ] and perfusion MRI [ 24 , 37 ] may detect abnormalities before CE appears. In conclusion, AD may depict the correlate for these early metabolic and micro-vascular changes.…”
Section: Discussionsupporting
confidence: 64%
“…The event of MT of a LGG into its anaplastic WHO III equivalent is timely unpredictable but nearly inevitable and may occur even after decades. This explains why imaging-based studies on predicting MT in the present literature are usually limited to small patient numbers [ 23 25 ] and why existing data on this topic is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other tests of LGG (e.g., molecular biomarkers testing) are also obtained to improve treatment planning. Several studies [ 9 12 ] have shown that codeletion of 1p/19q chromosome arms is a strong prognostic molecular marker for positive tumor response to chemotherapy and radiotherapy in LGG and associated with longer survival. Therefore, predicting 1p/19q status is crucial for effective treatment planning of LGG.…”
Section: Introductionmentioning
confidence: 99%
“…Iwadate et al [ 11 ] studied detection of 1p/19q codeletion from 11 C–methionine PET images and concluded that 11 C–methionine PET might help discriminate tumors with and without 1p/19q codeletion preoperatively. Bourdillion et al [ 12 ] presented prediction of anaplastic transformation in grade 2 oligodendrogliomas based on MR spectroscopy and 1p/19q status. They showed that choline/creatine ratio > 2.4 was associated with the occurrence of anaplastic transformation in patients without 1p/19q codeletion.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Bourdillion et al . used 1 H MRS analysis to identify a metabolic pattern that correlated to malignant transformation in low-grade tumours 19 . The Cho/Cr-ratio was found to be a powerful tool to monitor anaplastic transformation in low-grade tumours.…”
mentioning
confidence: 99%